Naming the moves: Using lateral reading to support students' evaluation of digital sources. Issue 5 (19th October 2020) - Walsh-Moorman, Elizabeth Ann; Pytash, Kristine E.; Ausperk, Marissa
Abstract: In this research study two professors and a classroom teacher collaborated to develop instructional moves to teach lateral reading, a digital source evaluation technique that involves conducting strategic quick research on sources of information. Results indicated that the introduction of lateral reading made students aware of the need to know more about the source of their information and encouraged a skeptical stance. The process of lateral reading was sometimes complicated by students' lack of background knowledge or web-searching skills. This study offers concrete strategies for scaffolding student thinking about digital source evaluation that one can embed in content area curriculum.